2018
DOI: 10.1039/c8en00328a
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Fe(ii) uptake/release by magnetite nanoparticles

Abstract: The reversible flow of Fe(ii) across the magnetite–solution interface impacts the stoichiometry and reactivity of magnetite nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…The higher pH values observed in presence of both nFe3O4 after 10 PVs (t-test, p-values<0.05) might be the consequence of an oxidation of the nFe3O4. Peng et al 43,44 demonstrated that at pH 6, proton-promoted dissolution yields the release of Fe 2+ (aq) from magnetite nanoparticles, following the equation 1: where the square represents a cationic vacancy due to diffusive migration of iron cations 43,44 . Although the pH values observed during the leaching with both particles are similar, in the 10 first PVs the pH values of the leaching solution observed in presence of nFe3O4@DMSA were lower.…”
Section: Resultsmentioning
confidence: 99%
“…The higher pH values observed in presence of both nFe3O4 after 10 PVs (t-test, p-values<0.05) might be the consequence of an oxidation of the nFe3O4. Peng et al 43,44 demonstrated that at pH 6, proton-promoted dissolution yields the release of Fe 2+ (aq) from magnetite nanoparticles, following the equation 1: where the square represents a cationic vacancy due to diffusive migration of iron cations 43,44 . Although the pH values observed during the leaching with both particles are similar, in the 10 first PVs the pH values of the leaching solution observed in presence of nFe3O4@DMSA were lower.…”
Section: Resultsmentioning
confidence: 99%
“…The surface properties of magnetite can be altered upon Fe(II)-recharge. Indeed, complex surface reactions can take place when stoichiometric magnetite is equilibrated with dissolved Fe(II), such as rapid atomic exchange 20 , redistribution of electron equivalents between bulk and the outermost surface of particles 21 , and surface-mediated electron transfer with redox-sensitive species in solution 22 . It is, therefore, necessary to thoroughly characterize both the bulk and surface of magnetite to accurately…”
Section: Introductionmentioning
confidence: 99%
“…XMCD spectra of magnetite typically show two negative peaks due to Fe(II) and Fe(III) on a O h site, and a positive one due to Fe(III) on a T d site, whose relative intensities allow determining the magnetite stoichiometry. For these reasons, XAS and XMCD at the Fe L 2,3 -edges were used in several studies to elucidate the structure and properties of magnetite surfaces 21,[24][25][26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…Nevertheless, it is likely that electron transfer between birnessite and sorbed Mn 2+ impacts Mn AOS and oxidative reactivity of birnessite under mildly acidic conditions. Our recent studies showed that electron injection from sorbed Fe(II) to magnetite (Fe 3 O 4 ) can change the structural Fe(II)/Fe(III) ratio and the reduction potential of magnetite without the formation of secondary mineral phases, the extent of which depends on solution pH, magnetite loading, and initial concentrations of aqueous Fe(II) and redox-active organic molecules [22,23]. Similarly, the interfacial electron transfer between birnessite and Mn 2+ may induce electron injection and delocalization in Mn octahedral layers of birnessite, even though no detectable secondary phases are formed.…”
Section: Introductionmentioning
confidence: 99%